Free Radicals and Diseases (IntechOpen, 2023)
The current volume entitled, "Free Radicals and Diseases" integrates knowledge in free radical-associated diseases from the basic level to the advanced level, and from the bench side to bed side. The chapters in this book provide an extensive overview of the topic, including free radical formations and clinical interventions.